Preventive cardiology insights into the prevention and treatment of cardiovascular disease - Foody, JoAnne Micale (Contemporary cardiology)
With the gradual transition from the technology-driven, intervention-oriented perspective of the last decade to a new, preventive, molecular-based perspective, Joanne Foody, MD, has amassed new preventive measures for use in everyday practices in this new edition of Preventive Cardiology. This new edition provides practical information for the management of patients at risk for cardiovascular disease and also offers an overview of the new paradigms in the pathophysiology of coronary artery disease (CAD). Divided into three parts, Part I focuses on the atherosclerotic process, the important central role of the endothelium in the maintenance of cardiovascular health, and the role of inflammation in CAD. Part II provides insights into gender-specific aspects of CAD risk and concentrates on traditional cardiovascular risk factors. Part III provides an overview of approaches for the identification of patients at risk for CAD events and reviews of stress testing in patients with CAD and the important role of antiplatelets in coronary disease. Preventive Cardiology: Insights Into the Prevention and Treatment of Cardiovascular Disease, Second Edition provides an overview of the exciting opportunities to prevent the progression, and in some instances to regress the process, of coronary atherosclerosis and incorporate these strategies into the daily practice of clinical medicine. This valuable new edition provides clinical cardiologists, internists, primary care providers, and allied health care professionals with the tools and understanding necessary for their practice in preventive cardiology. New paradigms in the pathophysiology of coronary artery disease - The unstable plaque - Endothelial function and insights for prevention - Inflammation and infection in coronary artery disease - Risk factors and their management in coronary artery disease - Low-density lipoprotein cholesterol and coronary artery disease - High-density lipoprotein cholesterol, triglycerides, and coronary artery disease - Management of hypertension - Diabetes mellitus, hyperinsulinemia, and coronary artery disease - Exercise in the prevention of coronary artery disease - Obesity and coronary artery disease - Tobacco as a cardiovascular risk factor - The implications of mental stress for cardiovascular disease - Women and coronary artery disease - Strategies for prevention - Subclinical atherosclerosis - Exercise testing and risk assessment - Aspirin and antiplatelet agents in the prevention of complications of coronary artery disease - Pharmacoeconomics of cardiovascular medicine - Innovative models for the delivery preventive cardiovascular care.